Exploring alternative tag visualizations. - Leow, Zheng Yu. (2010)
Collaborative tagging has been gaining in popularity in the last few years. Creators of these tagging systems frequently present their tag contents in the form of visualizations known as tag clouds. Past and recent research related to tag clouds includes user evaluations on various aspects of tag clouds, tag cloud enhancements, alternative tag visualizations, and alternative applications of tag clouds. Tag cloud enhancements tend to involve different ways of selecting tags, layout, coloring and positioning. The alternative visualizations generally focused on one or more of the following dimensions: temporal, social networking, tag inter-relationships and geographical. This study created alternative forms of tag visualizations based on a tree representation of the tag space. The tree map and radial tree layouts were used to visualize the tag space. The main reason for using these two layouts is because, as compared to other layouts, they are able to more efficiently utilize the display space. Two variations were created for both layouts: the first variation did not display details about the tagged items, whereas the second variation displayed the titles of the tagged items.